Pengaruh Qirā’āt Terhadap Penafsiran Ayat Pemberian Mut’ah dalam Kitab Tafsir Al-Qurthubī - Deski Ramanda; Syafruddin Syafruddin; Efrinaldi Efrinaldi; Edriagus Saputra; Dian Puspita Sari (Institut Agama Islam Negeri (IAIN) Curup, 2021)
Differences will not always have a negative impact, even differences in the qira'at of the Qur'an. Because of the difference in qirā'āt, it will enrich the meaning and of course will also affect the interpretation of the verses of the Qur'an and especially the verse giving mut'ah in the book of interpretation of the Qur'an. This research is library research, with reference to primary sources, namely the Kitab Tafsir Al-Qurthubī, while for secondary references, the authors use the books of ulūm al-Quran which discusses related to the concept of qirā'āt, journals and other books. The method that the author uses in this study, namely descriptive analysis method and to process and analyze data in this study used the content analysis method, with the aim of digging deeper into the content of written information in the book of Tafsir Al-Qurthubī. The results of this study found that the reading of qira'at greatly influences interpretation, including: first, explaining the meaning of the verse. Second, qira'at provides breadth of the meaning of the verse. Third, and qira'at can remove the problem from the meaning of the verse. And the influence of qira'at on the interpretation of the verse of giving mut'ah contained in Al-Baqarah: 236, namely giving mut'ah based on the ability of the husband by considering the wife's morals